Restrukturisasi Legal Standing Institusi Gereja: Analisis Manajemen Risiko dan Akuntabilitas Aset Pasca-Pemberlakuan PMA No. 13 Tahun 2025 - Suhartoyo Suhartoyo (Jurnal Pendidikan Indonesia, 2026)
This study is motivated by the need for legal certainty and accountability in managing Catholic Church institutions in Indonesia, particularly following the enactment of Minister of Religious Affairs Regulation No. 13 of 2025 concerning Catholic Religious Legal Entities (BHKK). The previous regulation based on Staatsblad 1927 is considered outdated and no longer compatible with modern administrative systems that emphasize transparency and digitalization. This research aims to analyze the restructuring of the Church’s legal standing and its implications for risk management and asset accountability. The study employs a normative juridical legal research method using statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials analyzed descriptively and analytically. The findings reveal that PMA No. 13 of 2025 strengthens legal certainty by formally recognizing BHKK as a legal subject, thereby enhancing legitimacy in asset management, contractual relations, and institutional activities. Furthermore, the regulation functions as a legal risk mitigation instrument that prevents personal liability of administrators due to administrative failures. In conclusion, the implementation of this regulation reinforces the legal standing of Catholic Church institutions and promotes transparent, accountable, and legally compliant organizational governance within the national legal system